2019
DOI: 10.1002/jmv.25653
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis virus B and C infections are associated with an increased risk of non‐Hodgkin lymphoma: A nested case‐control study using a national sample cohort

Abstract: BackgroundHepatitis B virus (HBV) and hepatitis C virus (HCV) are suspected of being associated with non‐Hodgkin lymphoma (NHL); however, persuasive data are lacking. Hence, a nested large‐population case‐control study was performed to investigate such associations in Koreans.MethodsData were collected from 929 patients with NHL and 3716 healthy subjects, who were matched 1:4 for age, sex, income, and region of residence, from the Korean Health Insurance Review and Assessment Service‐National Sample Cohort. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…A nested large-population case-control study in Korea investigated the suspected relationship between hepatitis and NHL. The results reported that the incidence of HBV and HCV in the NHL group (3.3% and 1.3%, respectively) was higher than that in the control group (0.9% and 0.3%, respectively; p < 0.001) [11]. In a previous study in Taiwan, chronic HCV infection was temporally associated with a twofold increase in the risk of lymphoid tumors from 2001 to 2005, especially the risk of NHL.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…A nested large-population case-control study in Korea investigated the suspected relationship between hepatitis and NHL. The results reported that the incidence of HBV and HCV in the NHL group (3.3% and 1.3%, respectively) was higher than that in the control group (0.9% and 0.3%, respectively; p < 0.001) [11]. In a previous study in Taiwan, chronic HCV infection was temporally associated with a twofold increase in the risk of lymphoid tumors from 2001 to 2005, especially the risk of NHL.…”
Section: Discussionmentioning
confidence: 80%
“…Among older adults, a registry-based case-control study for HCV infection and the risk of cancer indicated a positive association with diffuse large B-cell lymphoma (aOR, 1.57; 95% CI, 1.34-1.84) [36]. One study reported the adjusted ORs of HBV in patients with NHL who were <55 years compared with those who were ≥55 years-2.28 (p = 0.038) and 3.48 (p < 0.001), respectively-and the adjusted ORs for HCV in patients with NHL who were <55 years compared with those who were ≥55 years were 2.58 (p = 0.114) and 3.24 (p = 0.044), respectively [11]. The results of the present study indicate that patients with lupus erythematosus, human immunodeficiency virus, and organ transplant were all at a higher risk of developing NHL.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Chronic infection with HBV is a kind of pathological status which can cause chronic liver damage such as changes of liver-related immunity and inflammation (7)(8)(9)(10)(11). HBV infection has been well recognized to be one of the major causes of hepatocellular cancer (HCC) and associated with non-Hodgkin's lymphoma (12)(13)(14)(15). Moreover, some reports are obtainable regarding that whether HBV infection is associated with liver metastasis in some extrahepatic malignancies including colorectal cancer (CRC) and pancreatic cancer (PC).…”
Section: Introductionmentioning
confidence: 99%